Just making the subs, if M,X,c,P are given you have:
b=M-X-c-P
Let + is XOR
Is it possible to get back b if M, X, P is Given ??Code:b + X = d c + P = e d + e = M
if thats not possible is it possible if c is also Given . b is not possible to Be given.
If possible please tell teh expression. and I think its possible.
And please first try to solve if c is not given .
Thanks .
I think (I am not in touch of Maths for 2 years [I might be wrong])
m = d Xor e [m is given]
d = b Xor X
here to get the value of b we need to substitute d with b Xor X
and as e is not given we must substitute
but only relation of e is given is e = c Xor P
and that relates with c
we cant get rid of c .
I thought about another way also by Xoring e with c
So e Xor c = c Xor c Xor P but its not possible cause there is no other relations (only one relation) that relates with c.
So I thing Its not possible.